Extended quasiparticle approximation for relativistic electrons in plasmas - Morozov, V.G.; Ropke, G. (Condensed Matter Physics, 2006)
Starting with Dyson equations for the path-ordered Green’s function, it is shown that the correlation functions for relativistic electrons (positrons) in a weakly coupled non-equilibrium plasmas can be decomposed into sharply peaked quasiparticle parts and off-shell parts in a rather general form. To leading order in the electromagnetic coupling constant, this decomposition yields the extended quasiparticle approximation for the correlation functions, which can be used for the first principle calculation of the radiation scattering rates in QED plasmas.